REALITIES OF TRAINING OF EDUCATION MANAGERS IN KAZAKHSTAN (Journal of Educational Sciences, 2019)
Relevance of the research: the quality of education depends not only on the teacher, but also on the principal. For this reason today in the developed countries increasing emphasis is made on the problem of training for school leaders.Purpose of the article – to analyze the Kazakhstani practice of managerial training  in education, to carry out comparative analysis of the best foreign models of training of school leaders.Research methods: comparative analysis, questionnaire for principals. Results: the summarized  understanding of functions of the manager in education,  completion of analysis of foreign models of training of managers of education, substantiation for the necessity for development of leadership skills in principals, presentation of questionnaire results  and recommendations on the improvement of the system for retraining of education managers in Kazakhstan. The importance of the research is that the presented results can be considered when designing programs of training and retraining of education managers.Keywords: school leadership, design of programs, training system, strategies of developmentmanager, education manager, program design, training system, technology development